Graves' disease and Down's syndrome. Issue 2 (April 1983) - McCulloch, A J; Clark, F; Steele, N R
Abstract : A case is described of severe thyrotoxicosis occurring in a patient with Down's syndrome, in which behavioural disturbance was a marked but reversible phenomenon. In addition, we report that antibodies capable of stimulating the thyroid were detectable in the sputum of both the patient and his mother.